Bad economy, good teachers? The countercyclicality of enrolment Into Initial Teacher Training Programmes in the UK - Joshua Fullard (University of Essex, Institute for Social and Economic Research (ISER), 2021)
Using data from the Destination of Leavers from Higher Education (DLHE), we take advantage of the plausibly exogenous variation in the unemployment rate, by field of study, at time of graduation to investigate the impact of labour market condition on teacher supply, measured by enrolment onto an Initial Teacher Training Programme (TTP). We find that labour market conditions have no effect on the probability that a graduate will go into a TTP. However, heterogeneity analysis suggests that periods of high unemployment impact the composition of graduates who enrol with effects on diversity (more male graduates and more ethnic minority graduates), subject specific shortages (more Physics graduates) and quality (more graduates from Russell Group Universities).
Keywords: E32; I23; J22; J23; 330; Teacher Supply; Business Cycle; Graduates